The two exact solutions of mc017-1.jpg for mc017-2.jpg are: mc017-10.jpg and mc017-11.jpg. To solve the equation mc017-1.jpg for mc017-2.jpg, we first need to simplify the expression under the square root. We have:-3.jpg. To solve for x, we can square both sides of the equation: mc017-5.jpg Expanding the terms on the left-hand …To solve a system of equations by elimination, write the system of equations in standard form: ax + by = c, and multiply one or both of the equations by a constant so that the coefficients of one of the variables are opposite. Then, add or subtract the two equations to eliminate one of the variables. Solve the resulting equation for the ...Find the distance covered by a bus moving at 70km/hour in 3 hour 30 min. 7. Find the measure of angle x in each of the following figures: (i) 66degree . Advertisement. Find an answer to your question Which ordered pair (a, b) is a solution to the given system of linear equations? es027-1.jpg -13,-4 -13,4 -4,-13 -4,13.The system of equation that can be graphed to find the solution is. ------> equation A. -------> equation B. Using a graphing tool. see the attached figure. the solution is the point. therefore. the answer is. The system of equation that can be graphed to find the solution is.Let’s review the idea of ”number of solutions to equations” real quick. Basically, an equation can have: Exactly one solution, like 2x = 6. It solves as x = 3, no other options. No solutions, like x+6 = x+9. This would simplify to 6 = 9, which is, ummm, not true, so no solutions. Infinitely many solutions, such as 3x = 3x.The solution of the given equation is (5/2, 1/3) Step-by-step explanation: It is given an equation, (2x - 5)(3x - 1) = 0. To find the solution of given equation (2x - 5)(3x - 1) = 0 means that, either (2x - 5) = 0 or (3x - 1) = 0. If 2x - 5 = 0. 2x = 5. x = 5/2. or 3x - 1 = 0. 3x = 3. x = 1/3. Therefore the solution of the given equation is (5/ ...We're asked to find the number of solutions to this system of equations: − 6 x + 4 y = 2 3 x − 2 y = − 1. Interestingly, if we multiply the second equation by − 2 , we get the first equation: 3 x − 2 y = − 1 − 2 ( 3 x − 2 y) = − 2 ( − 1) − 6 x + 4 y = 2. In other words, the equations are equivalent and share the same graph.Solve. Quadratic equation. x2 − 4x − 5 = 0. Trigonometry. 4sinθcosθ = 2sinθ. Linear equation. y = 3x +4. Arithmetic. 699 ∗533. Matrix. [ 2 5 3 4][ 2 −1 0 1 3 5] …richard bought 3 slices of cheese pizza and 2 sodas for $8.75. Jordan bought 2 slices of cheese pizza and 4 sodas for $8.50. How much would an order of 1 slice of cheese pizza and 3 sodas cost? A. $3.25 B. $5.25 C. $7.75 D. $7.25 Lorraine writes the equation shown. es027-1.jpg. She wants to describe the equation using the term relation and the term function. The equation represents. a relation and a function. The temperature in degrees Celsius, c, can be converted to degrees Fahrenheit, f, using the equation mc026-1.jpg. x^2+8x-6x-48=0. Now solve the like terms: x^2+2x-48=0. Now we will solve this quadratic equation by factoring: The first terms has coefficient 1. So 1 will be multiplied by the constant term 48. 1*48= 48. Now we have to find out the two values whose product is 48 and whose sum or difference is 2(middle term). 8*6 = 48. 8-6 = 2. Now break the ...As a member of the LinkedIn business network you can upload a profile photo that appears at the top of your profile page and in search results when other LinkedIn users search for ...Given is a systems of equations in two variables a and b. 3a+b=10 -4a-2b=2. Let us solve this and find solution. We can do this by elimination method. I equation x 2 gives . Add these two equations to get. 2a = 22. Divide by 2. We get a=11. Substitute in I equation. 3(11)+B=10. b =10-33 =-23. Hence solution set is (11,-23) Option C is the right ...-2(-4) + 3(13) = -8 + 39 = 31 - 14 = 17 - 14 = 3. In the second equation, a - 4b = -3, if we substitute a = -4 and b = 13, we get:-4 - 4(13) = -4 - 52 = -56 = -3. Both equations hold true when we substitute the values a = -4 and b = 13. Hence, the ordered pair (-4, 13) is a solution to the system of linear equations. Learn more about Linear ...richard bought 3 slices of cheese pizza and 2 sodas for $8.75. Jordan bought 2 slices of cheese pizza and 4 sodas for $8.50. How much would an order of 1 slice of cheese pizza and 3 sodas cost? A. $3.25 B. $5.25 C. $7.75 D. $7.25A solution of a system of two linear equations is represented by an ordered pair. To determine if an ordered pair is a solution to a system of two equations, we substitute the values of the variables into each equation. If the ordered pair makes both equations true, it is a solution to the system.Sep 25, 2020 · To Find : Which ordered pair (x, y) is the solution to the given system of linear equations (–2, 1) (–0.5, 0.5) (0.5, –0.5) (1, –2) Solution: 3x+y=1 5x+y=3 => 5x + y - (3x + y) = 3 - 1 => 2x = 2 => x = 1. 3(1) + y = 1 => 3 + y = 1 => y = - 2 (1 , - 2) (1,-2) ordered pair is the solution to the given system of linear equations . Learn More: The ordered pair (a, b) that is the solution to the given system of equations can be found by substituting the values of a and b into the equations and checking if they satisfy both equations. Let's check each option: (4, 2): When we substitute a = 4 and b = 2 into the equations, we get 4(4) + 2 = 18 and 2(4) - 3 = 5. Therefore, this is not a ...The solution to a quadric equation are x=2 and x=7. If k is a nonzero constant which of the following must be equal to the quadratic equation . verified. Verified answer. Jonathan and his sister Jennifer have a combined age of 48. If Jonathan is twice as old as his sister, how old is Jennifer. star. 4.8/5.The Equation: es027-1.jpg. Given the equation depicted in the image below: Our goal is to determine the value of 'g' that makes this equation true. Isolating the Variable. To find the value of 'g', we need to isolate the variable on one side of the equation. Let's simplify the equation by multiplying both sides by -1:-1 * (g + 7) = -1 * (-3g - 10)Solve by Substitution Calculator. Step 1: Enter the system of equations you want to solve for by substitution. The solve by substitution calculator allows to find the solution to a system of two or three equations in both a point form and an equation form of the answer. Step 2: Click the blue arrow to submit.2. gcf and lcm of 35 and 45? 3. find GCF of 24 and 32 4. Find the GCF of 45 and 60. 5. tolong bantuin no 1 dan 2 pake caranya jangan jawab ngasal yang benar aku followtengtang GCF dan LCM 6. ¶¶¶ QUIZ #187 ¶¶¶• english version• big point=====1. factorized 187.218 into the prime factorization!2. what is GCF of 187, 231 and 440 ? 7.May 31, 2023 · richard bought 3 slices of cheese pizza and 2 sodas for $8.75. Jordan bought 2 slices of cheese pizza and 4 sodas for $8.50. How much would an order of 1 slice of cheese pizza and 3 sodas cost? A. $3.25 B. $5.25 C. $7.75 D. $7.25 Dec 7, 2019 · richard bought 3 slices of cheese pizza and 2 sodas for $8.75. Jordan bought 2 slices of cheese pizza and 4 sodas for $8.50. How much would an order of 1 slice of cheese pizza and 3 sodas cost? A. $3.25 B. $5.25 C. $7.75 D. $7.25 These are three possible solutions to the equation. (0,7),(1,9),(2,11) ( 0, 7), ( 1, 9), ( 2, 11) Enter YOUR Problem. Free math problem solver answers your algebra, …You might be interested in. What are the solutions of the equation: x2 – 1 = 15? x = ± sqrt 14 x = ± sqrt 15 x = ±4 x = ±8. star. 5 /5.Hence to solve the equation, factorise. 3x2 + 2x −5 = 0. (3x +5)(x −1) = 0. The 2 factors of the equation are (3x +2) and (x −1). With (3x + 5) = 0 and (x − 1) = 0. Solve for x to find the solutions. Answer link. (3x + 5) = 0 x= - (5/3) x - 1 = 0 x= 1 Hence, solution is x = - (5/3) or x=1 The question gives you an equation 3x^2 + 2x -5 = 0.A system of linear equations consists of two or more equations made up of two or more variables such that all equations in the system are considered simultaneously. The solution to a system of linear equations in two variables is any ordered pair that satisfies each equation independently. See Example 11.1.1.In mathematics, to find the ordered pair (a, b) that is a solution to a given system of linear equations, one must use either substitution or elimination method. Suppose you are given the system of equations: 5a - 2b = 16. 3a + 4b = 27. One can use substitution or elimination method to solve for 'a' and 'b'. The solution would be the …Explanation: The original equation mentioned in your question is missing, but I'll assume you are referring to solutions of the equation x² = √ ( 2x² - 1 ). This equation can be solved by first simplifying the condition as 2 (x² - 1)² ≤ 1. Following the standard method for solving quadratic equations, we can use the quadratic formula -b ...We will solve larger systems of equations later in this chapter. An example of a system of two linear equations is shown below. We use a brace to show the two equations are grouped together to form a system of equations. { 2 x + y = 7 x − 2 y = 6. A linear equation in two variables, such as 2 x + y = 7, has an infinite number of solutions.It turns out that choice B is the answer. (3,1) means that a = 3 and b = 1. Plug in a = 3 and b = 1 into the first equation. 2a - 5b = 1. 2*3 - 5*1 = 1.... replace 'a' with 3, replace b with 1. 6 - 5 = 1. 1 = 1. we get a true equation, so we have confirmed the first equation. Do the same for the second equation.Moises is determining the solution to the system of equations that is show below. Equation representing line A: mc018-1.jpg Points on line B: (3, –12) and (9, –24) Step 1: Determine the slope for B: mc018-2.jpg Step 2: Determine the y-intercept for B: mc018-3.jpg Step 3: Write the equation in slope-intercept form: mc018-4.jpgWrite these fractions in order from smallest to largest: 1 2/5 26/20 12/10 Amaka and uche shared a total number of 21 apples. Amaka gets twice the number uche gets.2.7: Solve Linear Inequalities.Why are there so many different image formats on the web? What, for example, is the difference between a GIF and a JPG image? Advertisement It certainly is true that there are lot...2xx − 3 + 3 = 6x − 3 (x≠3) We have said x≠3 to avoid a division by zero. Let's multiply through by (x − 3): 2x + 3(x−3) = 6. Bring the 6 to the left: 2x + 3(x−3) − 6 = 0. …The equation given in this question is x ^6 + 6x^3 + 5 = 0, which is not a standard quadratic equation. However, it can be turned into quadratic form by substitution. Let's consider y = x^3. Our equation becomes y^2 + 6y + 5 = 0. This can be factored as (y + 1)(y + 5) = 0, so the roots for y are -1 and -5. Remembering that y = x ^3, we set x^3 ...Answer: g=3 . Explanation: Match coefficients of the terms accordingly: g =3-x=3-x Solve the equations: g=3 Answer: g=3. Click to rate:We're asked to find the number of solutions to this system of equations: − 6 x + 4 y = 2 3 x − 2 y = − 1. Interestingly, if we multiply the second equation by − 2 , we get the first equation: 3 x − 2 y = − 1 − 2 ( 3 x − 2 y) = − 2 ( − 1) − 6 x + 4 y = 2. In other words, the equations are equivalent and share the same graph.A student showed the steps below while solving the equation mc026-1.jpg by graphing. Step 1: Write a system of equations: mc026-2.jpg. Step 2: Use the change of base formula to rewrite the equations: mc026-3.jpg. Step 3: Graph the two equations: mc026-4.jpg. Step 4: Identify the x-value at the point of intersection: mc026-5.jpg.2.7: Solve Linear Inequalities. What are the coordinates of the point? A. (3, 6) B. (−3, −6) C. (6, −3) D. (−3, 6) Sara has a certain amount of money in her bank account on Monday morning. During the week, she writes a check for $43.75, withdraws $135 from an. Which ordered pair (a,b) is a solution to the given system of linear equations. Get the answers you need, now! You'll get a detailed solution from a subject matter expert that helps you learn core concepts. See Answer See Answer ... (8a^(-6)b^(-3)), assuming that a!=0 and b!=0. Her simplified expression is bel -(1)/(2)a^(4)b What exponent should Marina use for b ? -7 -1 1 7. There are 2 steps to solve this one. Who are the experts? Experts have been ...Using the quadratic formula, which is x = (-b ± √(b² - 4ac)) / (2a), where a = 1, b = 0.0211, and c = -0.0211, we can substitute these values into the formula to find the values of x. After simplifying, we get: x = (-0.0211 ± √(0.0211² - 4(1)(-0.0211))) / (2(1)) x = (-0.0211 ± √(0.00044421 + 0.08484)) / 2. x ≈ (-0.0211 ± √0. ...In the one you referenced, Sal is using the first equation: -x-3y=9. If you use x=0, the equation becomes: -0-3y=9, then solve for Y. -3y=9. y=-3. This creates one point for graphing the first line. The point is (0, -3). Sal repeats this process using other values of X to find 2 points for each line.Convert Images to PDF for free online. Our JPG to PDF Converter turns any image file into a custom PDF file (No size limits, no watermarks). Easy-to-use online JPG to PDF converter. No installation–works in your browser. Free conversion without registration.Learn for free about math, art, computer programming, economics, physics, chemistry, biology, medicine, finance, history, and more. Khan Academy is a nonprofit with the mission of providing a free, world-class education for anyone, anywhere.Dec 13, 2023 · Solution. Square the first term to get (9x)2 = 81x2 ( 9 x) 2 = 81 x 2. Square the last term to get 42 = 16 4 2 = 16. Subtract the square of the last term from the square of the first term to find the product of 81x2 − 16 81 x 2 − 16. Exercise 1.2.7 1.2. 7. Multiply (2x + 7)(2x − 7) ( 2 x + 7) ( 2 x − 7). Answer. The quadratic equation only contains powers of x that are non-negative integers, and therefore it is a polynomial equation, and in particular it is a second degree polynomial equation since the greatest power is two. Quadratic equations can be solved by factoring, by completing the square, by using the quadratic formula, or by graphing ...The solution to a quadric equation are x=2 and x=7. If k is a nonzero constant which of the following must be equal to the quadratic equation . verified. Verified answer. Jonathan and his sister Jennifer have a combined age of 48. If Jonathan is twice as old as his sister, how old is Jennifer. star. 4.8/5.Learn for free about math, art, computer programming, economics, physics, chemistry, biology, medicine, finance, history, and more. Khan Academy is a nonprofit with the mission of providing a free, world-class education for anyone, anywhere.The solution (s) to a quadratic equation can be calculated using the Quadratic Formula: The "±" means we need to do a plus AND a minus, so there are normally TWO solutions ! The blue part ( b2 - 4ac) is called the "discriminant", because it can "discriminate" between the possible types of answer: when it is negative we get complex solutions.The traditional hiring process puts job seekers at a disadvantage. Rare is the candidate who is able to play one prospective employer against the other in a process that will resul...Dec 8, 2021 · Add the equations together to cancel the b-terms, then solve for a. 2a - 5b = 1. 3a + 5b = 14 +_____ 5a - 0 = 15. 5a = 15. a = 3. Next, plug 3 for a into either of the equations and solve for b. 2a - 5b = 1. 2(3) - 5b = 1. 6 - 5b = 1 - 5b = -5. b = 1. Lastly, check all work by plugging both values for their respective variables. 2a - 5b = 1. 2 ... A student uses the equation mc013-1.jpg to represent the speed, s, in feet per second, of a toy car driving around a circular track having an angle of incline mc013-2.jpg, where mc013-3.jpg. To solve the problem, the student used the given value of mc013-4.jpg to find the value of mc013-5.jpg and then substituted the value of mc013 …We will solve larger systems of equations later in this chapter. An example of a system of two linear equations is shown below. We use a brace to show the two equations are grouped together to form a system of equations. { 2 x + y = 7 x − 2 y = 6. A linear equation in two variables, such as 2 x + y = 7, has an infinite number of solutions.PowerBand Solutions News: This is the News-site for the company PowerBand Solutions on Markets Insider Indices Commodities Currencies StocksThe equation is an illustration of indices and exponents. The common base used to rewrite each side of the expression is 2. How to determine the common base. The equation is given as:. Rewrite the above equation using the laws of indices and exponents as:. The above equation means that:. This means that, the common base when the …2 albums and 5 singles B. Study with Quizlet and memorize flashcards containing terms like Which system of equations can be graphed to find the solution (s) to 4x2 = x2 - 7?, Carlos graphs the equations mc014-1.jpg and mc014-2.jpg and generates the graph below. Which conclusion is supported by the graph?, The constraints of a problem are listed ...Jun 11, 2020 · The required value of exponent should Marian used to be is 7.. Given that, Marina has the expression . Where a ≠0, b≠0. The new expression = . Assuming the exponent of b = x. We have to determine, richard bought 3 slices of cheese pizza and 2 sodas for $8.75. Jordan bought 2 slices of cheese pizza and 4 sodas for $8.50. How much would an order of 1 slice of cheese pizza and 3 sodas cost? A. $3.25 B. $5.25 C. $7.75 D. $7.25Dec 8, 2021 · Add the equations together to cancel the b-terms, then solve for a. 2a - 5b = 1. 3a + 5b = 14 +_____ 5a - 0 = 15. 5a = 15. a = 3. Next, plug 3 for a into either of the equations and solve for b. 2a - 5b = 1. 2(3) - 5b = 1. 6 - 5b = 1 - 5b = -5. b = 1. Lastly, check all work by plugging both values for their respective variables. 2a - 5b = 1. 2 ... Her simplifed expression is below.. - 1/2 a^4b^( ) The exponent of the variable b in Marina's solution should be -7 -1 1 7. 125. Solution. Jacob. University of Nigeria · Tutor for 2 years. Answer: 7 . Her simplifed expression is below.. - 1/2 a^4b^( ) The exponent of the variable b in Marina's solution should be -7 -1 1 7. 125. Solution. Jacob. x^2+8x-6x-48=0. Now solve the like terms: x^2+2x-48=0. Now we will solve this quadratic equation by factoring: The first terms has coefficient 1. So 1 will be multiplied by the constant term 48. 1*48= 48. Now we have to find out the two values whose product is 48 and whose sum or difference is 2(middle term). 8*6 = 48. 8-6 = 2. Now break the ...Oct 16, 2018 · A scale drawing of a rectangular park had a scale of 1 cm = 100 m. 6.2 cm 11.7 cm What is the actual area of the park in meters squared? can someone pls help with this, I would appreciate it chevron left Solve. Quadratic equation. x2 − 4x − 5 = 0. Trigonometry. 4sinθcosθ = 2sinθ. Linear equation. y = 3x +4. Arithmetic. 699 ∗533. Matrix. [ 2 5 3 4][ 2 −1 0 1 3 5] …Sep 25, 2020 · To Find : Which ordered pair (x, y) is the solution to the given system of linear equations (–2, 1) (–0.5, 0.5) (0.5, –0.5) (1, –2) Solution: 3x+y=1 5x+y=3 => 5x + y - (3x + y) = 3 - 1 => 2x = 2 => x = 1. 3(1) + y = 1 => 3 + y = 1 => y = - 2 (1 , - 2) (1,-2) ordered pair is the solution to the given system of linear equations . Learn More: richard bought 3 slices of cheese pizza and 2 sodas for $8.75. Jordan bought 2 slices of cheese pizza and 4 sodas for $8.50. How much would an order of 1 slice of cheese pizza and 3 sodas cost? A. $3.25 B. $5.25 C. $7.75 D. $7.255 terms. abbyg3808. Preview. Unit Test 4. 13 terms. Kaje04. Preview. Unit Test / Unit Test (I only got an 88% btw) 25 terms. keelieasalter. Preview. Sporting Group.Step 1: Enter the system of equations you want to solve for by substitution. The solve by substitution calculator allows to find the solution to a system of two or …2xx − 3 + 3 = 6x − 3 (x≠3) We have said x≠3 to avoid a division by zero. Let's multiply through by (x − 3): 2x + 3(x−3) = 6. Bring the 6 to the left: 2x + 3(x−3) − 6 = 0. …Click here 👆 to get an answer to your question ️ The solutions to the equation 2cos θ =0.2 for 0≤ θ ≤ 2π are 1.47 radians and 1.67 radians. ... The solutions to the equation 2cos θ =0.2 for 0≤ θ ≤ 2π are 1.47 radians and 1.67 radians. (Give your answers correct to 3 s.f., with the lower number first.) 158. Solution. Samuel ... 1.1 Factoring: mc 27-jpg Theory : A difference of two perfect cubes, a 3 - b 3 can be factored into (a-b) • (a 2 +ab +b 2) Proof : (a-b)•(a 2 +ab+b 2) = a 3 + a 2 b + ab 2-ba 2-b 2 a-b 3 = a 3 +(a 2 b-ba 2)+(ab 2-b 2 a)-b 3 = a 3 + 0 + 0-b 3 = a 3-b 3 Check : m 1 is not a cube !! Ruling : Binomial can not be factored as the difference of ... Derivation of Quadratic Formula. A Quadratic Equation looks like this: And it can be solved using the Quadratic Formula: That formula looks like magic, but you can follow the steps to see how it comes about. 1. Complete the Square. ax2 + bx + c has "x" in it twice, which is hard to solve. But there is a way to rearrange it so that "x" only ...Find the distance covered by a bus moving at 70km/hour in 3 hour 30 min. 7. Find the measure of angle x in each of the following figures: (i) 66degree . Advertisement. Find an answer to your question Which ordered pair (a, b) is a solution to the given system of linear equations? es027-1.jpg -13,-4 -13,4 -4,-13 -4,13. Example 15.2. Solutions of equations: a) A solution for x − 4 = 6 is x = 10 because the LHS evaluated at x = 10 is 10 − 4 = 6 which is equal to the R H S. b) A solution for 5 x − 6 = 4 x + 2 is x = 8 because the LHS evaluated at x = 8 is 5 ( 8) − 6 = 40 − 6 = 34 and the RHS evaluated at x = 8 is 4 x + 2 = 4 ( 8) + 2 = 32 + 2 = 34, and ... What are the coordinates of the point? A. (3, 6) B. (−3, −6) C. (6, −3) D. (−3, 6) Sara has a certain amount of money in her bank account on Monday morning. During the week, she writes a check for $43.75, withdraws $135 from an. Which ordered pair (a,b) is a solution to the given system of linear equations. Get the answers you need, now!How to solve your equation. To solve your equation using the Equation Solver, type in your equation like x+4=5. The solver will then show you the steps to help you …are factors of the quadratic equation. This implies that the quadratic equation is of the form, We were also told that is a non zero constant. This means that we can use k to multiply the whole equation and the solution will not be affected. Our equation now becomes, Hence the correct answer is A.To solve for x we set each factor =0 and solve for x. divide each term by 3. Add 4 on both sides. Subtract 5 on both sides. So x values are -5 and 4. arrow right. Explore similar answers. messages. Talk to an Expert about this answer. The 4 term has a coefficient of -3, and the x-term has a coefficient of 1. The expression does not have a constant term, which expression could she have written? - x-y^2-3y. - What, if any, was Jane's Mistake? - Jane incorrectly evaluated (-2)^2 in step 2. - How many terms are in the algebric expression. -7+12x4-5y^8+x? It turns out that choice B is the answer. (3,1) means that a = 3 and b = 1. Plug in a = 3 and b = 1 into the first equation. 2a - 5b = 1. 2*3 - 5*1 = 1.... replace 'a' with 3, replace b with 1. 6 - 5 = 1. 1 = 1. we get a true equation, so we have confirmed the first equation. Do the same for the second equation.Which expression is equivalent to mc016-1.jpg? B. The equation mc024-1.jpg shows the relationship between a planet's orbital period, T, and the planet's mean distance from the sun, A, in astronomical units, AU. If planet Y is twice the mean distance from the sun as planet X, by what factor is the orbital period increased?. First we distribute the equation into two equation. LA system of linear equations consists of two or To solve a system of equations by substitution, solve one of the equations for one of the variables, and substitute this expression into the other equation. Then, … Derivation of Quadratic Formula. A Quadratic Equation looks You'll get a detailed solution from a subject matter expert that helps you learn core concepts. ... loading. Question: What value of g makes the equation true? (x+7)(x-4)=x^(2)+gx-28 -11 -3 3 11. What value of g makes the equation true? (x+7)(x-4)=x^(2)+gx-28 -11 -3 3 11. There are 2 steps to solve this one. Who are the experts? Experts have ... Nov 30, 2016 · To solve for x we set e...

Continue Reading## Popular Topics

- Dec 7, 2019 · richard bought 3 slices of cheese pi...
- What are equations? Equation is a formula that expresses the equality...
- Option C: y + 2 = (x –2) simplifies to y = x, which does not pass thr...
- Final answer: The equations 2x² + 6x + 9, x² + 3x + 12, and ...
- 2xx − 3 + 3 = 6x − 3 (x≠3) We have said x≠3 to avoid a divisi...
- x+y=5 , x-y=1. Isolate the x. x - y (+y) = 1 (+y) ...
- Answer: (2u + 1)(u – 3) = 0 is equivalent to the given equat...
- The LHS evaluated at \(x=-2\) is \((-2)^{2}-2(-2)+1=4+4+1=9\)...